Unusual Photochemical C-N Bond Cleavage in the Novel Methyl 2-Chloro-3-methyl-2H-azirine-2-carboxylate - Gomez Zavaglia, Andrea (2006)
The structure, preferred conformers, vibrational spectrum, and photochemical behavior of the novel azirine, methyl 2-chloro-3-methyl-2H-azirine-2-carboxylate (MCMAC) were investigated in low-temperature matrixes and in the neat solid amorphous state by infrared spectroscopy and quantum-chemical calculations. Two conformers of the compound were observed in argon, krypton, and xenon matrixes, in agreement with the DFT(B3LYP)/6-311++G(d,p) and MP2/6-311++G(d,p) theoretical calculations. Both conformers were found to exhibit the carboxylic ester group in the cis conformation, differing in the arrangement defined by the O=C-C-Cl dihedral angle (cis and trans, for Ct and Cc forms, respectively). The Ct conformer was found to be the most stable conformer in the gaseous phase as well as in both argon and krypton matrixes, whereas the more polar Cc conformer became the most stable form in the xenon matrix and in the neat solid amorphous phase. In situ broadband UV (lambda > 235 nm) excitation of matrix-isolated MCMAC led to azirine ring C-C and C-N bond cleavages, the latter process corresponding to the most efficient reaction channel. The photochemical cleavage of the C-N bond had never been previously observed in the case of aliphatic 2H-azirines. Two electron withdrawing substituents (methoxycarbonyl group and chlorine atom) are connected to the azirine ring in the novel MCMAC azirine. The simultaneous presence of these two groups accelerates intersystem crossing toward the triplet state where cleavage of the C-N bond takes place. The primary photoproducts resulting from the C-N and C-C ring-opening reactions were also found to undergo further photochemical decarbonylation or decarboxylation reactions.